The spatio-temporal properties of calcium transients in hippocampal pyramidal neurons in vitro - Shkryl, Vyacheslav M. (Frontiers in Cellular Neuroscience, 2022)
The spatio-temporal properties of calcium signals were studied in cultured pyramidal neurons of the hippocampus using two-dimensional fluorescence microscopy and ratiometric dye Fura-2. Depolarization-induced Ca2+ transients revealed an asynchronous delayed increase in free Ca2+ concentration. We found that the level of free resting calcium in the cell nucleus is significantly lower compared to the soma, sub-membrane, and dendritic tree regions. Calcium release from the endoplasmic reticulum under the action of several stimuli (field stimulation, high K+ levels, and caffeine) occurs in all areas studied. Under depolarization, calcium signals developed faster in the dendrites than in other areas, while their amplitude was significantly lower since larger and slower responses inside the soma. The peak value of the calcium response to the application of 10 mM caffeine, ryanodine receptors (RyRs) agonist, does not differ in the sub-membrane zone, central region, and nucleus but significantly decreases in the dendrites. In the presence of caffeine, the delay of Ca2+ signals between various areas under depolarization significantly declined. 30% of the peak amplitude of Ca2+ transients at prolonged electric field stimulation corresponded to calcium release from the ER store by RyRs, while short-term stimulation did not depend on them. 20 µM dantrolene, RyRs inhibitor, significantly reduces Ca2+ transient under high K+ levels depolarization of the neuron. RyRs-mediated enhancement of the Ca2+ signal is more pronounced in the central part and nucleus compared to the sub-membrane or dendrites regions of the neuron. In summary, using the ratiometric imaging allowed us to obtain additional information about the involvement of RyRs in the intracellular dynamics of Ca2+ signals induced by depolarization or electrical stimulation train, with an underlying change in Ca2+ concentration in various regions of interest in hippocampal pyramidal neurons.